2018
DOI: 10.3390/bioengineering5040076
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-Mediated Delivery of Drugs and Nucleic Acids for Anti-Angiogenic Cancer Therapy: Current Landscape and Remaining Challenges

Abstract: Angiogenesis, sprouting of new blood vessels from pre-existing vasculatures, plays a critical role in regulating tumor growth. Binding interactions between integrin, a heterodimeric transmembrane glycoprotein receptor, and its extracellular matrix (ECM) protein ligands govern the angiogenic potential of tumor endothelial cells. Integrin receptors are attractive targets in cancer therapy due to their overexpression on tumor endothelial cells, but not on quiescent blood vessels. These receptors are finding incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 129 publications
0
14
0
Order By: Relevance
“…Additionally, integrin receptors are overexpressed in tumor ECs and play a key role connecting the cell cytoskeleton to the extracellular matrix protein ligands such as arginine-glycine-aspartic acid (RGD). This binding interaction between integrin and protein ligands is an important mechanism during the angiogenesis of tumor endothelial cells (52).…”
Section: Cancer and Angiogenesismentioning
confidence: 99%
“…Additionally, integrin receptors are overexpressed in tumor ECs and play a key role connecting the cell cytoskeleton to the extracellular matrix protein ligands such as arginine-glycine-aspartic acid (RGD). This binding interaction between integrin and protein ligands is an important mechanism during the angiogenesis of tumor endothelial cells (52).…”
Section: Cancer and Angiogenesismentioning
confidence: 99%
“…It participates in activation and migration of endothelial cells, mediates endothelial cell proliferation and inhibits endothelial cell apoptosis, thus promoting angiogenesis 23-25. Integrin can also participate in the transformation, growth, invasion, metastasis and apoptosis of cancer cells by transmitting specific signals or inducing gene expression 26,27. Xu, H.M. et al found that ES-2 had good anti-angiogenetic activity in vitro , but its activity in vivo was moderated 28.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, a micellar delivery vehicle decorated with an anti-angiogenic peptide has been shown to inhibit α v β 3 mediated neovascularization in endothelial cells (100). Several anti-cancer drugs have also been developed against integrin ligands or by using integrintargeted encapsulated nanoparticles as vehicles to unload drugs into the vasculature of several tumors (101).…”
Section: Integrin-targeted Therapiesmentioning
confidence: 99%